Improving Students’ Speaking Skills through Role-Play Technique at SMKN 1 Tenggarong - Laily Nur Janah; Ade Ismail Ramadhan Hamid; Khusnul Khatimah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
Speaking proficiency is essential for vocational school students because it supports effective communication in workplace contexts. However, students at SMKN 1 Tenggarong face difficulties in English speaking due to limited vocabulary, fear of making mistakes, low confidence, and classroom practices that emphasize repetition rather than interaction. This study aimed to examine the effectiveness of the role-play technique in improving students’ speaking skills. A quasi-experimental design was applied involving two groups, each consisting of 36 students. The experimental group received instruction through role-play activities, while the control group was taught using conventional methods. Both groups completed pre-tests and post-tests to measure improvement in speaking performance. The treatment was conducted over six instructional meetings using job-related role-play scenarios. The data were analyzed using the Wilcoxon Signed Rank Test with the assistance of SPSS. The results showed a significant improvement in the experimental group, with a post-test mean score of 85.33, compared to 66.83 in the control group. The p-value of 0.000 indicated a statistically significant difference between the two groups. These findings suggest that role-play effectively enhances students’ speaking ability by increasing confidence, providing meaningful interaction, and supporting practical language use in vocational English contexts